PERBEDAAN GRADASI TERHADAP KARAKTERISTIK MARSHALL CAMPURAN BETON ASPAL LAPIS PENGIKAT (AC-BC) - Makmun R. Razali; Bambang Sugeng Subagio (Universitas Bengkulu, 2019)
This research described the result of laboratory investigation toward the performance of Asphalt Concrete Binder Course (AC-BC) mixture with three types gradation : above the fuller curve (mix. A), below the fuller curve (mix. B) and combination between above and below the fuller curve (mix. C). All of the mixtures were designed according to Marshall Method. Test results showed that all mixtures met the requirements from Asphalt Concrete Binder Course (AC-BC) mix properties according to Marshall Parameter. According Marshall method had optimum bitumen content 5,60% (mix A), 6,10% (mix B)) and 6,30% (mix C).